"Human Telephone Lines": Flag Post Mail Relay Runners in British Southern Cameroon (1916–1955) and the Establishment of a Modern Communications Network. (10th October 2014) - Gam Nkwi, Walter; de Bruijn, Mirjam
Abstract The flag post mail relay runners, a communications system established in Cameroon during British colonial rule, laid the foundations for the communications structure of this colonial state. They were a remnant of a pre-colonial communications system and, with the advancement of "modern" communications structures such as roads, telephone lines, and post houses, the flag post runner gradually disappeared. This article explores the role of the runners for the colonial administration in Cameroon and is based mostly on archival research. It describes the runners' system and how it influenced the colonial communications landscape. In addition, the questions of how these runners were involved in the colonial state and what forms of resistance emerged among runners are analysed. Finally, the article discusses the degree to which the subsequent construction of roads, telegraphic communications, and postal networks reflected the role played by mail runners in the British colonial period up to the 1950s.